Optimizing Clinical Postgraduate Training: Perspectives of Postgraduate Alumni Regarding Their Residency Training at Mbarara University of Science and Technology, Uganda - Tibaijuka L; Atimango L; Kajjimu J; Owaraganise A; Kamukama N; Kato PK; Mugyenyi GR; Kayondo M; Boatin AA; Ngonzi J (Advances in Medical Education and Practice)
Leevan Tibaijuka,1,2 Lorna Atimango,1 Jonathan Kajjimu,1 Asiphas Owaraganise,3 Nixon Kamukama,4 Paul Kalyebara Kato,1 Godfrey Rwambuka Mugyenyi,1 Musa Kayondo,1 Adeline Adwoa Boatin,5 Joseph Ngonzi1 1Department of Obstetrics and Gynecology, Faculty of Medicine, Mbarara University of Science and Technology, Mbarara, Uganda; 2Department of Obstetrics and Gynecology, Mbarara Regional Referral Hospital, Mbarara, Uganda; 3Clinical Division, Infectious Diseases Research Collaboration, Kampala, Uganda; 4Office of the Deputy Vice Chancellor Academic Affairs, Mbarara University of Science and Technology, Mbarara, Uganda; 5Department of Obstetrics and Gynecology, Massachusetts General Hospital, Boston, Massachusetts, USACorrespondence: Leevan Tibaijuka, Department of Obstetrics and Gynecology, Mbarara University of Science and Technology, P.O. Box 1410, Mbarara, Uganda, Tel +256776868084, Email ltibaijuka@must.ac.ugBackground: Understanding alumni satisfaction and the competencies gained during university training can guide improvements in education quality, particularly in higher education institutions. This study at Mbarara University of Science and Technology (MUST) explored the factors influencing alumni decisions, their residency experiences, and their levels of satisfaction. Additionally, it provided recommendations for improving graduate training programs.Methods: We conducted a mixed methods study from June to September 2022, employing an online survey and in-depth interviews (IDIs). The survey was distributed via Email and WhatsApp to MUST residency alumni, with 12 participants selected for IDIs. Descriptive summary statistics and thematic analysis were used to analyze the data.Results: Ninety-five MUST alumni (34.3% response rate) participated, predominantly males (80%), aged 31– 40 (69%), and Ugandans (72%). Most graduated after 2018 (83%) in surgical specialties such as obstetrics/gynecology (38%) and general surgery (19%). Factors influencing residency program choice included practice-oriented study programs (61%), fields of specialization (55%), university or departmental reputation (46%), and admission standards (32%). While 80% were satisfied with the learning and teaching, only 50% expressed satisfaction with the infrastructure. IDIs revealed satisfaction due to compassionate faculty and strong university partnerships but criticized limited study facilities, difficult adaptation for international students, insufficient hands-on training, human resource shortages, and limited technology. Recommendations included collaborative mentorship, increased hands-on training exposure, more partnerships, and enhanced infrastructure and technology support.Conclusion: Most alumni were satisfied with their residency training despite infrastructure dissatisfaction, finding it well-aligned with their work and beneficial for their careers. Our study highlights opportunities for implementing proposed improvements to enhance residency training. It suggests that similar universities should conduct post-graduate tracers to evaluate trainee experiences and inform future directions.Keywords: residency training, choice, perspectives, recommendations for improvement, MUST, graduates, tracer study, Uganda